Accessibility and Inclusivity in Online Education: A Comparative Study of Policies and Practices in Australia - Taylor, Mia (International Journal of Online and Distance Learning, 2024)
Purpose: The aim of the study was to investigate the accessibility and inclusivity in online education: a comparative study of policies and practices in Australia. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study compared Australian policies and practices in online education accessibility and inclusivity, revealing notable gaps in implementation despite progress. It emphasized the necessity of comprehensive policies and ongoing educator training to address diverse student needs effectively. Overall, it highlighted the importance of continual improvement to ensure equitable access for all students in online education. Unique Contribution to Theory, Practice and Policy: Social model of disability, universal design for learning (UDL) & critical pedagogy may be used to anchor future studies on the accessibility and inclusivity in online education: a comparative study of policies and practices in Australia. Develop guidelines and best practices for inclusive course design and delivery in online education, tailored to the Australian context. Advocate for the integration of accessibility and inclusivity mandates into national and institutional policies governing online education in Australia.